(untitled) (Alternautas, 2024)
Spanish people can detect my Mexican accent as soon as I open my mouth, and it’s interesting to see their reactions during my travels through that country. Most Spaniards are kind and curious. But I do remember a taxi driver who convivially told me that, to be sure, Spain had done horrible things to Mexico, but that I should still think of Spain like a father — a drunk and abusive father, in his words, but a father nonetheless. One can take such remarks about colonialism in stride and with good humor when they come from a taxi driver. But it is difficult to swallow similar arguments when they come from historians like Fernando Cervantes, author of Conquistadores: A New History of Spanish Discovery and Conquest.